Awareness, knowledge, attitude, perception, and utilization of complementary and alternative medicines (CAMs) in the common population of Dammam, Saudi Arabia - Wasim Ahmad; Ayaz Ahmad; Yousif A Hassan; Nisha Sivapalan; Shainy Daniel; Ruby A Anna; Fatimah Al-Shurfa; Fatimah Albaharnah; Amjad Al-Hayyan (Wolters Kluwer Medknow Publications, 2022)
Background: Complementary and alternative medicine (CAM)/natural products/herbs are frequently used for therapeutic purposes as a homemade remedy in Saudi Arabia. The use of CAMs is rising globally. However, special attention or precaution should be paid when using CAMs along with other drugs. Objective: The current study aims to examine the perception, attitude, knowledge, and awareness of the general population about CAMs and their utilization. Material and Methods: A cross-sectional study was conducted in March 2020 in the Dammam region of Saudi Arabia. The study included both the gender participants of the general population of Dammam, Saudi Arabia. The questionnaire contains the following sections including socio-demographic data, knowledge, attitude, and behavior of participants related to CAMs, and the prevalence of CAMs utilization in Dammam. Results: Participants were closely sex-matched (male: 50.93% and female: 49.07%), consisting of 97.1% Saudis and only 2.9% expats. The response rate was 67%; out of 559 participants, only 375 participants completed the questionnaire. Approximately 53% of participants had some knowledge of CAMs. Mass media (media/web/internet, advertisement, and television (TV), academic education, and family friends/relative represented the main source of the CAMs information (50%, 8.8%, and 15.2%, respectively). Among 77.3% of the participants, one of their family members has used some form of CAMs earlier. 90% of the participants or their family members using CAMs reported that olive oil (95.7%), green tea (89.1%), thyme (85.3%), cinnamon bark (84.8%), star anise (84.5%), and black seeds (78.4%) were the most used CAMs. Participants used CAMs for cold (28.3%), cough (14%), constipation (11.97%), ease of menstruation (10.8%), diarrhea (9.87%), and fever (8.62%). Approximately 75% of participants did not observe any side effects. Only 1% of participants reported that the CAMs are not useful therapeutically whereas the majority of the participants reported them as very useful (32.7%), useful (45.5%), and good (20.7%). Conclusion: Current study demonstrates that there is a positive attitude and perception toward CAMs. It is influenced by their traditional use as well. However, a community awareness program is essential for the adverse effects of CAMs.